Análise do projeto sippem no município de Russas - CE - Oliveira, Jorge Michel de Lima (Universidade Federal Rural do Semi-Árido, 2019)
This research describes an analysis of the SIPPEM Project (Pedagogical Intervention System in Portuguese and Mathematics), created by the Municipal Department of Education of the Municipality of Russas in the year 2013. The SIPPEM project aims to implement actions that enable students of the 9th grade the development of skills and abilities in the Portuguese and Mathematics disciplines, as well as assisting in the raising of results in large-scale evaluations such as SPAECE and SAEB, which functions as a diagnosis of education in Brazil. Among the actions, namely: the diagnostic evaluation, initial step of the pedagogical work; the literacy and numbering workshops, which will systematically address content in which students have the greatest learning difficulties; the continuous training of teachers, which provides pedagogical guidance, assisting in the preparation of didactic material that will be used in the application of the workshops; Evaluation of Learning, which is also done in meetings of continuing training. The research instrument used is: questionnaire to teachers of Portuguese Language and Mathematics of the SIPPEM Project in 2018, questionnaire to the teachers of the schools involved in the Project and interview with the Coordinator of Mathematics of the Municipal Secretary of Russas. The analysis of the results shows the contributions of the Project in terms of improvement in student learning and in the indexes that analyze the situation of education. In addition, survey data allow discussions on common and divergent points that have been reported by parties involved in the Project's logistics
Keywords: Formação continuada; Ensino e aprendizagem; Intervenções pedagógicas; Avaliações; Continuing education; Teaching and learning; Pedagogical interventions; Assessments; CIENCIAS EXATAS E DA TERRA::MATEMATICA